2010
DOI: 10.4103/0974-8520.68208
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sri Lankan traditional decoction of Katuwelbatu Deduru Katukadi in treatment of Kaphaja Shira Shula (chronic sinusitis)

Abstract: Kaphaja Shira Shula is one of the Shiro Roga. Chronic sinusitis is inflammation of the sinuses behind the forehead, cheeks, and eyes, which continues for a long time or keeps recurring. Kaphaja Shira Shula can be correlated with Chronic Sinusitis. The decoction of Katuwelbatu Deduru Katuka is mentioned in Watika Prakaranaya, a book on Sri Lankan Traditional Medicine. The ingredients of this decoction are Solanum xanthocarpum, Cuminum cyminum, Nigella sativa, Picroihiza kurrota and Clerodendrum serratum. But in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Inclusion criteria were not the same in the four trials. Two studies, by Ediriweera (Ediriweera, Rathnayaka, Premakeerthi, & Weerasinghe, ) and Maragalawaththa (Maragalawaththa, Ediriweera, & Chandimarathne, ), were based only on clinical symptoms as reported by patients without any standard questionnaire. The other two studies (Jiang [20] and Vazifehkah [23]) used diagnostic criteria based on the European position paper on rhinosinusitis and nasal polyps (EPOS) and sinus endoscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Inclusion criteria were not the same in the four trials. Two studies, by Ediriweera (Ediriweera, Rathnayaka, Premakeerthi, & Weerasinghe, ) and Maragalawaththa (Maragalawaththa, Ediriweera, & Chandimarathne, ), were based only on clinical symptoms as reported by patients without any standard questionnaire. The other two studies (Jiang [20] and Vazifehkah [23]) used diagnostic criteria based on the European position paper on rhinosinusitis and nasal polyps (EPOS) and sinus endoscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Among these 10 selected comparative clinical trials (pre-treatment n = 387; end of treatment n = 363) [13,14,15,16,17,18,19,20,21,22], 8 were RCTs and 02 were nRCTs. Out of these 10 trials, 5 RCTs and 2 nRCTs were included in quantitative analysis (pre-treatment n = 287; end of treatment n = 259).…”
Section: Resultsmentioning
confidence: 99%
“…Out of these 10 trials, 5 RCTs and 2 nRCTs were included in quantitative analysis (pre-treatment n = 287; end of treatment n = 259). Among them, 4 trials were having three arms and 3 trials were having two arms and blinding was reported in only one trial[22]. However, none of the trials mentioned concealment methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Royal jelly, grapes, and figs are also reinforcing the brain and the nervous system (17)(18)(19)(20). The positive effects of cumin (C. cyminum) and black cumin (N. sativa) on the treatment of vertigo, sinusitis, and post nasal discharge are expressed in numerous articles (21,22). Coriander is also used in Ayurveda as a CNS tonic to treat vertigo (23,24).…”
mentioning
confidence: 99%